Development of Restful API Mental Health Application with Microservices Architecture Using Google Cloud Platform - Zidan, Muhamad; Mardianto, Is; Salim, Agus (ULTIMATICS, 2025)
Circle application is an application on the Android operating system that is engaged in the field of mental health. The application requires a server that receives requests to fulfill the features contained in the application, therefore a server is needed one that can be scaled easily and quickly so that there are no long delays in requests, and it is hoped that the code base is easy to maintain and can be rapidly deployed.